A feasibility study for developing 3D sketching concept in virtual reality (VR) environment - Ramimian, Farzad Pour; Ibrahim, Rahinah; Zaky Jaafar, Mohd Fakri (Faculty of Design & Architecture, Universiti Putra Malaysia, 2008)
There is limited digital media available to encompass conceptual design which requires spontaneous and flexible design tools. The constraint is causing less digital integration during the architectural conceptual and engineering design stages. This paper presents the results of an ethnography research on understanding how design collaboration, design transactions and knowledge flow characteristics between studio masters and their students are supported by available technologies in a studio project in Malaysia. The study found three types of external representation modes used by designers: Full Manual, Mixed and Full Digital. The study revealed the inflexibility of traditional geometric modeling tools within intuitive ideations. On the other hand, it also observed the shortcomings of conventional manual sketching tools for articulating design ideas and translating tacit knowledge into explicit knowledge in complex design problems. Results from this study support further studies towards implementing 3D sketching in Virtual Reality (VR) environment to digitally integrate the conceptual architectural-engineering design process.